High Glucose Induces Autophagy through PPARγ-Dependent Pathway in Human Nucleus Pulposus Cells - Chang Jiang; Shuhao Liu; Yuanwu Cao; Hongping Shan (PPAR Research)
Diabetes mellitus is a multiorgan disorder affecting many types of connective tissues, including bone and cartilage. High glucose could accelerate the autophagy in nucleus pulposus (NP) cells. In our present study, we investigated whether peroxisome proliferator-activated receptor γ (PPAR-γ) pathway is involved into autophagy regulation in NP cells under high glucose condition. After NP cells were treated with different high glucose concentrations for 72 hours, the rate of autophagy increased. Moreover, the levels of PPARγ, Beclin-1, and LC3II were significantly increased and p62 was significantly decreased compared to control group. Then, NP cells were treated with high glucose plus PPARγ agonist or PPARγ antagonist, respectively. The rate of autophagy and the levels of Beclin-1 and LC3II increased, but p62 decreased when PPARγ agonist was used. On the contrary, the rate of autophagy and the levels of Beclin-1 and LC3II decreased, while p62 increased when PPARγ antagonist was added. These results suggested that autophagy induced by high glucose in NP cells was through PPARγ-dependent pathway.